Constitutional Court Decree No 90/Puu-XII/2023 Provisions on Age Requirements for Presidential and Vice Presidential Candidates in the Principles of the State of Law and Pancasila Democracy - Sifa, Nurul Ash; Rapo, Kasilda (Dynamics of Politics and Democracy, 2024)
Purpose: This study examines the legal consequences of Constitutional Court Decision No. 90/PUU-XXI/2023, which adds new requirements for presidential and vice-presidential candidates, and analyzes its implications for the constitutional system and the balance of power between state institutions in Indonesia. Research methodology: Using a normative juridical approach, this research draws upon statute analysis, constitutional theory, and judicial interpretation. It evaluates the decision based on Hans Kelsen’s legal hierarchy theory and the principle of judicial restraint within a constitutional democracy. Results: The findings show that the Constitutional Court, through this decision, has expanded its interpretive role beyond judicial review, effectively performing a legislative function. This has resulted in the creation of a new norm that was not previously regulated by law. The decision also raises concerns about the erosion of judicial neutrality and the risk of institutional imbalance, particularly between the judiciary and the legislature. Conclusions: The decision disrupts the principle of separation of powers and may set a precedent for overreach by the judiciary. It calls into question the boundaries of judicial authority and its role in upholding democratic values and the rule of law. Limitations: The study is limited to a normative-doctrinal analysis and does not include comparative perspectives or empirical data. Contribution: This paper contributes to the discourse on constitutional law by emphasizing the need for judicial neutrality and reinforcing the importance of checks and balances in maintaining a democratic constitutional order.